2018
DOI: 10.1021/acsami.8b05811
|View full text |Cite
|
Sign up to set email alerts
|

Design of Hetero-Nanostructures on MoS2 Nanosheets To Boost NO2 Room-Temperature Sensing

Abstract: Molybdenum disulfide (MoS), as a promising gas-sensing material, has gained intense interest because of its large surface-to-volume ratio, air stability, and various active sites for functionalization. However, MoS-based gas sensors still suffer from low sensitivity, slow response, and weak recovery at room temperature, especially for NO. Fabrication of heterostructures may be an effective way to modulate the intrinsic electronic properties of MoS nanosheets (NSs), thereby achieving high sensitivity and excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(136 citation statements)
references
References 59 publications
5
127
0
Order By: Relevance
“…Normally, the defect-dominated process on the surface of MoS 2 contributes to the signicant response and recovery times because of the high adsorption energy of the target gas with the defects as reactive sites. 36 Previous works reported that sensors based on pristine MoS 2 of different nanostructures have incomplete recovery at RT possibly because of the high adsorption energy of NO 2 on the MoS 2 surface or the strong binding between NO 2 and the reactive sites of MoS 2 . 17,37 However, some other works indicated that in spite of slow rates of gas adsorption and desorption, the pristine MoS 2 -based sensors showed the complete recovery at RT to target gases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Normally, the defect-dominated process on the surface of MoS 2 contributes to the signicant response and recovery times because of the high adsorption energy of the target gas with the defects as reactive sites. 36 Previous works reported that sensors based on pristine MoS 2 of different nanostructures have incomplete recovery at RT possibly because of the high adsorption energy of NO 2 on the MoS 2 surface or the strong binding between NO 2 and the reactive sites of MoS 2 . 17,37 However, some other works indicated that in spite of slow rates of gas adsorption and desorption, the pristine MoS 2 -based sensors showed the complete recovery at RT to target gases.…”
Section: Resultsmentioning
confidence: 99%
“…The gas-sensing characteristics of the MoS 2 nanostructures can be explained by the Langmuir-Hinshelwood mechanism for chemical reaction of the tested gas with adsorbed oxygen molecules on the surface of the sensing layer, leading to change in the sensor's resistance. 36,42,43 As shown in Fig. 7(a), when the p-type semiconducting MoS 2 nanostructures were exposed to ambient air, oxygen molecules were adsorbed on the MoS 2 surface and electrons were captured from the valence band of the MoS 2 to form the oxygen ion species (O 2 À , O À and O 2À ) (eqn (5)-(8)) as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the representative TMDC, MoS 2 shows a high carrier mobility (60 cm 2 /V s at 250 K), a layer-dependent bandgap (1.2-1.8 eV), a high transistor on/off ratio (~ 10 8 ), and reasonable environmental stability [11]. Recent reports have demonstrated that 2D MoS 2 is a desirable channel material in FET sensor with breakthroughs in sensing performance for various analytes including NO 2 [12][13][14][15], NH 3 [16,17], chemical vapor [18,19], metal ion [20][21][22], small molecule [23][24][25], as well as biomaterials such as nucleic acid [26][27][28][29], protein [30][31][32], and microorganism [33]. Compared with MOSFET sensors, 2D-TMDCbased FET sensors normally show higher sensitivities due to the 2D nanosheet structure of TMDC.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it can realize low temperature NO 2 sensing by the UV‐light activation or without the presence of the UV‐light irradiation. However, for the case of the absence of the UV‐light activation, the NO 2 sensors usually show the very slow response/recovery speed, which is bad for the practical detection application. Alternatively, the emergence of UV‐light illuminated mode can effectively avoid above shortcomings, because it offers a very low working temperature and fast response/recovery speed.…”
Section: Introductionmentioning
confidence: 99%